If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2 + x = 2x + 6 Combine like terms: 5 + 2 = 7 7 + x = 2x + 6 Reorder the terms: 7 + x = 6 + 2x Solving 7 + x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + x + -2x = 6 + 2x + -2x Combine like terms: x + -2x = -1x 7 + -1x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + -1x = 6 + 0 7 + -1x = 6 Add '-7' to each side of the equation. 7 + -7 + -1x = 6 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 6 + -7 -1x = 6 + -7 Combine like terms: 6 + -7 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 5x+3=7x-5 | | 8x^2=50x-50 | | 10x^2-11x-35=0 | | 4y+9=7y-15 | | -3(-15)+20(-19)= | | 9s^2+12s=-4 | | 3+x=90-x | | C=0.06s+450 | | k^3+4k^2+k+6=0 | | .50t+6=7 | | m+(-8)=12 | | v^2-6v+6= | | 2x^2-4x-126=0 | | v^2+6v+6= | | 100x+132=50x+132 | | 9x^6+76x^2+x-7=0 | | 20x^2-12x=x | | 3x^2+10x=-6 | | w^2+42W=0 | | 3x(4-6)=10 | | 4b=88 | | 21x+13=3x-5 | | f+25=81 | | 3c=75 | | .5(10y+4)=17 | | e+53=73 | | 7e=147 | | 4b+6y^2=0 | | 4b+6y^2= | | y+9=21 | | 2x-2=3x-2 | | -5y+6x=21 |